Family Policy in Hungary How to Improve the Reconciliation between Work and Family? - Hemmings, Philip (OECD Publishing, 2007)
Hungarian family policy focuses on providing generous options to take time off work to look after children. This system not only contributes to Hungary's low employment rate but encourages long separation from the labour market, has largely failed to significantly influence fertility rates and is relatively expensive to run. This paper looks at how to shift the policy focus towards reconciling work and family life. Reasons for under-provision in childcare by local governments are discussed and recommendations for further central-government intervention to improve supply are made. Recommendations for reform are also made regarding the complex system of family cash benefits and leave allowances
Keywords: Economics; Hungary